Proceedings of the 6th International Conference on Sensor Networks 2017
DOI: 10.5220/0006203601680173
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Synthesis of Routing Protocols and Synthetic Mobility Modeling for MANET

Abstract: Many performance analyses are already done with a lot of flaws. But, they do not look to all influenced constraints. In this study, we aim to summarize several parameters into 90 different scenarios with an average of 1350 simulated files. That shows results of three performance metrics combined with five mobile ad hoc routing protocols under three synthetic mobility models. All these parameters are applied to two dissimilar simulation areas. Basing on one exhaustive analysis with all these details like this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Conversely, when the obtained lines have acceptable or big margin fluctuations, the minimum does not equal 0 and the maximum comes closer to the total number of nodes. This reflects the fact that the validated mobility model is more stable and steady with time that will lead to satisfactory outcomes in the performance analysis [3].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Conversely, when the obtained lines have acceptable or big margin fluctuations, the minimum does not equal 0 and the maximum comes closer to the total number of nodes. This reflects the fact that the validated mobility model is more stable and steady with time that will lead to satisfactory outcomes in the performance analysis [3].…”
mentioning
confidence: 89%
“…Royer, Melliar-Smith, and Moser [9] noticed that, in random waypoint models, the density recurrently fluctuates with time, as depicted in Figure 3a, with a moderate fluctuation between 0 and 11 nodes. However, this issue at most affects the performance of other models [3]. This feature shows the independent mobility of mobile nodes.…”
Section: Density Wave Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of mobility models relays on the fact that they are used for simulating and evaluating mobile wireless networks overall performance and to design and assess algorithms and protocols which are based on them. Frequent mobility represents one of those challenging issues where it is deeply examined by considering highly dynamic mobile networks, leading the network mobility models to aim at characterizing the nodes movement (Tomasini et al 2017;Ibadah et al 2017). Several researchers have demonstrated that the adopted motion model significantly impaets the whole network performance (Karamshuk et al 2011).…”
Section: Introductionmentioning
confidence: 99%